Development of outdoor learning environments at elementary and middle schools in Rock Hill, South Carolina, USA. Issue 1 (3rd July 2019) - Wojcik, Janet R.; Bell, Thomas; Center, Danielle; McAden, Nicole
ABSTRACT: When new schools are built in the United States, they are often constructed on large parcels of land in suburban areas to account for the building footprint and automobile parking. Even if the school may be near residential neighbourhoods, there may still not be good connectivity of sidewalks and trails for students to walk and bicycle to school, relying on school buses and family automobiles, contributing to traffic and pollution. Therefore, there is a need to increase physical activity for students while they are at the school site besides traditional physical education classes. Outdoor active learning environments can address education standards across a variety of subjects such as physical education, science, history, math, and social studies and allow students to experience nature. There are options for schools located in non-walkable or non-bikeable areas to increase physical activity for students, faculty/staff and open community use by the public. This case study describes a process where schools in Rock Hill, South Carolina, USA, applied for a mini-grant to get a site plan to develop outdoor physical activity learning environments at the schools and success stories of plan implementation as well as challenges that could benefit other communities.